Measurement of User Satisfaction for Gamification-based Programming E-Learning Platform using End-user Computing Satisfaction Method - Pradana, Fajar; Setyosari, Punaji; Ulfa, Saida; Hirashima, Tsukasa; Saputra, Mochamad Chandra (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
HSS Learning is a learning media innovation in the form of a gamification-based e-learning platform to support the learning process in programming. HSS Learning has been applied to web design and programming courses, primarily on HTML and CSS topics. This study uses a quantitative model using a descriptive approach to measure the satisfaction level of HSS Learning users—measurement of user satisfaction using End-user Computing Satisfaction (EUCS). The variables used in this research are content, format, ease of use, timeliness, and accuracy. Data collection used a questionnaire consisting of 12 questions, with the number of participant data being 264 participants. The results show that the overall level of user satisfaction reaches 4.30 at level 5 (very strong). The results of this study can be used as a material evaluation for the application of instructional media in the programming field.